The Digital Age and Its Discontents Critical Reflections in Educatione - Stocchetti, Matteo (Helsinki University Press, 2020)
"Three decades into the 'digital age', the promises of emancipation of the digital 'revolution' in education are still unfulfilled. Furthermore, digitalization seems to generate new and unexpected challenges - for example, the unwarranted influence of digital monopolies, the radicalization of political communication, and the facilitation of mass surveillance, to name a few. This volume is a study of the downsides of digitalization and the re-organization of the social world that seems to be associated with it. In a critical perspective, technological development is not a natural but a social process: not autonomous from but very much dependent upon the interplay of forces and institutions in society. While influential forces seek to establish the idea that the practices of formal education should conform to technological change, here we support the view that education can challenge the capitalist appropriation of digital technology and, therefore, the nature and direction of change associated with it. This volume offers its readers intellectual prerequisites for critical engagement. It addresses themes such as Facebook's response to its democratic discontents, the pedagogical implications of algorithmic knowledge and quantified self, as well as the impact of digitalization on academic profession. Finally, the book offers some elements to develop a vision of the role of education: what should be done in education to address the concerns that new communication technologies seem to pose more risks than opportunities for freedom and democracy."